High-compression-strain platinum alloy nanometer material and preparation method and application thereof
By forming a rare earth metal oxide layer on the conductive carbon carrier and depositing PT and transition metals, the catalysis of rare earth oxides is used to increase the amount of transition metal, solving the low catalytic activity of platinum alloy materials in existing technology. The problem realizes the preparation of platinum alloy nanomaterials with high compression strain and high catalytic activity.
Patent Information
- Application Number
- CN202411509952.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-01-28
AI Technical Summary
The prior art is difficult to prepare platinum alloy nanomaterials with high compression strain, resulting in low catalytic activity and poor stability, and it is difficult to apply to hydroxide fuel cells and methanol fuel cells.
By forming a rare earth metal oxide layer on the conductive carbon carrier, PT and transition metals are deposited on the surface of the layer, and the catalysis of rare earth oxides is used to induce more transition metals to integrate into the PT crystal, reduce the PT lattice constant, and generate high high Compression strain.
It significantly improves the catalytic activity and stability of platinum alloy nanomaterials, and enhances its application performance in fuel cells.
Smart Images

Figure CN119381467A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of fuel cell catalysts and relates to a high compressive strain platinum alloy nano material and a preparation method and application thereof. Background Art
[0002] Energy shortages and environmental problems caused by fossil energy consumption are the main driving force for the development of clean energy. Hydrogen-oxygen fuel cells using hydrogen as fuel and direct methanol fuel cells using methanol as fuel have the characteristics of high energy conversion efficiency, zero pollution emissions and environmental friendliness. They are the most important clean energy batteries today and are also considered to be one of the ways to solve energy and environmental problems. These two new energy batteries require a large amount of Pt nanomaterials to catalyze oxygen reduction and methanol oxidation reactions. However, Pt nanomaterials face many challenges such as high cost, slow electrocatalytic kinetics, low catalytic activity and poor stability due to CO poisoning and Ohlsworth ripening.
[0003] Numerous studies have shown that alloying Pt with transition metals M (M = Ni, Co, Fe and Ru, etc.) is one of the most effective ways to improve the catalytic activity and stability of Pt nanocatalytic materials and reduce material costs. The alloying of Pt and M refers to the incorporation of transition metals M, whose atomic radius is smaller than that of Pt, into the Pt lattice to form a Pt-M metal bond and cause the Pt lattice constant to decrease and produce compressive strain. Under the action of ligand effect and strain effect, the transition metal M adjusts the adsorption strength of oxygen-containing intermediate species by optimizing the electronic structure of Pt, thereby improving the catalytic performance of Pt alloy materials. Therefore, one of the strategies to improve the catalytic performance of Pt alloy materials is to increase the alloying degree of Pt alloy materials. The higher the alloying degree of Pt alloy, the more transition metals are incorporated into the Pt lattice, which reduces the Pt lattice constant and produces higher compressive strain, thereby promoting the catalytic performance of Pt alloy materials.
[0004] At present, the preparation method of carbon-supported Pt alloy nanocatalyst materials mainly involves simultaneously reducing Pt salt precursor molecules and transition metal precursor molecules, so that Pt and transition metals form alloys and are deposited on carbon carriers to obtain PtM alloy nanocatalyst materials. However, it is very difficult to prepare Pt alloy nanomaterials with small particle size (<8nm) and high compressive strain by incorporating as many transition metals as possible into Pt to improve the alloying degree of PtM alloy. The main reason is that the reduction potential of Pt (0.799V) is greatly different from that of transition metals such as Ni (-0.29), Co (-0.282V), Fe (-0.447V) and Ru (-1.33V), so Pt is reduced at a fast rate while transition metals are reduced at a slow rate. In the process of Pt ions and transition metal ions being reduced to form PtM alloy, the nucleation and growth rate of Pt atoms is fast while the nucleation and growth rate of transition metal atoms is slow, resulting in a small number of transition metal atoms integrated into the Pt lattice, and a large amount of excess unalloyed transition metals will remain, which ultimately leads to a low degree of alloying of the prepared PtM alloy, and it is difficult to obtain Pt alloy nanomaterials with small nanoparticle size and high compressive strain. To this end, the main methods currently used are: (1) selecting chemical reagents with strong reducing properties (such as potassium borohydride, butyl lithium) and increasing the heat treatment temperature; (2) increasing the feed ratio of transition metal to Pt during the preparation of PtM alloy, that is, adding excess transition metal to solve the above problems. However, the use of strong reducing agents and increasing the heat treatment temperature will cause the size of PtM alloy nanoparticles to grow, while increasing the feed ratio of transition metals will result in too much unalloyed transition metals remaining in the preparation process. Removing these residual metals will cause environmental pollution and increase costs.
[0005] Therefore, it is necessary to provide a high compressive strain platinum alloy nanomaterial and its preparation method and application. By increasing the amount of transition metal integrated into the Pt lattice and improving the alloying degree of Pt and transition metal, a high compressive strain platinum alloy nanomaterial is prepared, so that the catalytic activity, stability and other properties of the platinum alloy nanomaterial are improved, so that it can be used in hydrogen and oxygen fuel cells and methanol fuel cells, and can play a more effective and long-lasting catalytic role, thereby helping to improve the performance of the fuel cell. Summary of the invention
[0006] In order to overcome the problems in the background technology, the present invention forms a rare earth metal oxide layer by depositing rare earth metal oxide nanoparticles on a conductive carbon carrier, and then deposits Pt and transition metals on the surface of the rare earth oxide layer. In the process of forming the platinum alloy, the catalytic effect generated by the valence change characteristics of the rare earth metal oxide is utilized to induce the incorporation of more transition metals with small atomic radius into the Pt lattice, thereby reducing the Pt lattice constant and generating high compressive strain, while enhancing the fixation effect of the rare earth oxide on the Pt alloy nanoparticles, thereby promoting the catalytic activity and stability of the Pt alloy nanomaterial.
[0007] In order to achieve the above object, the present invention is implemented by the following technical solutions:
[0008] In one aspect, the present invention provides a method for preparing a high compressive strain platinum alloy nanomaterial, the preparation method comprising the following steps:
[0009] (1) A conductive carbon carrier, a morphology control agent, and a surfactant are added to a mixed liquid of ethanol and ultrapure water, and after ultrasonic treatment, a carbon carrier suspension is obtained.
[0010] (2) Under stirring conditions, adding the rare earth metal precursor solution to the carbon support suspension obtained in step (1), then performing ultrasonic mixing, and then adding the alkaline solution to obtain a mixed solution.
[0011] (3) After the mixed solution is subjected to ultrasonic and stirring treatments in sequence, the mixed solution is subjected to a hydrothermal reaction to deposit rare earth oxide nanoparticles on the surface of the conductive carbon support to form a rare earth oxide layer. After the reaction, a carbon support / rare earth oxide nanoparticle composite is obtained. The rare earth oxide nanoparticles are mainly one of CeO2, PrO2, TbO2, Sm2O3, Eu2O3 and Yb2O3, and the size of the rare earth oxide nanoparticles is 1 to 10 nm.
[0012] (4) adding the carbon carrier / rare earth oxide nanoparticle complex to a mixed solution of a platinum precursor and a transition metal precursor, and performing ultrasonic treatment and stirring in sequence to obtain a mixture slurry.
[0013] (5) The mixture slurry is subjected to a hydrothermal reaction treatment or a hydrogen reduction heat treatment to alloy the platinum with the transition metal and deposit it on the surface of the rare earth oxide layer to obtain a high compressive strain platinum alloy nanomaterial. The pickling can be performed using one of acetic acid, sulfuric acid, hydrochloric acid, perchloric acid, oxalic acid or nitric acid, with an acid concentration of 0.1 to 10 mol / L. The pickling is performed at 30 to 80° C. for a total of 1 to 10 hours, and stirring is performed during the pickling process.
[0014] Preferably, when the rare earth metal element in the rare earth metal precursor exchanges electrons with the non-metallic element to form a compound, there is a metal valence change. The rare earth metal elements that meet the above requirements are Ce, Pr, Tb, Sm, Eu and Yb, and their precursors mainly include cerium fluoride, cerium nitrate, cerium sulfate, ammonium cerium sulfate, cerium bromide, cerium iodide, cerium acetylacetonate, cerium chloride, cerium fluoride, cerium nitrate, cerium sulfate, ammonium cerium sulfate, cerium bromide, cerium iodide, cerium acetylacetonate, cerium chloride, praseodymium chloride, praseodymium iodide, praseodymium fluoride, praseodymium nitride, praseodymium nitride, praseodymium nitrate, praseodymium sulfate, terbium chloride, terbium acetate, terbium fluoride, terbium iodide, terbium bromide, samarium chloride, samarium fluoride, samarium acetate, samarium iodide, samarium bromide, europium fluoride, europium nitride, europium chloride, europium nitrate, europium sulfate, etc. The rare earth metal precursor solution is a solution prepared by dissolving the rare earth metal precursor in a solvent such as water. Non-metallic elements mainly include oxygen elements and the like.
[0015] Preferably, the conductive carbon carrier includes a solid carbon carrier and / or a porous carbon carrier, wherein the solid carbon carrier is one of Cabot XC-72 and conductive carbon black; and the porous carbon carrier is one of Ketjen Black EC-300J, Ketjen Black EC-600JD, acetylene black and Cabot BP2000.
[0016] Preferably, the morphology control agent is one of anhydrous citric acid, sodium citrate, potassium citrate, calcium citrate, ammonium citrate, diammonium hydrogen citrate, stearic acid, sodium dodecylbenzene sulfonate, quaternary ammonium compound, lecithin, amino acid type, betaine type, alkyl glucoside, fatty acid glyceride, fatty acid sorbitan and polysorbate, and the mass ratio of the morphology control agent to the conductive carbon carrier is 1 to 10:1.
[0017] Preferably, the surfactant is one of hexadecyltrimethylammonium bromide, hexadecyltrimethylammonium chloride, hexadecyl sodium sulfate, dihexadecyltrimethylammonium bromide, octadecyltrimethylammonium bromide, sodium octadecyl sulfate, heptadecyltrimethylammonium bromide, tetradecyltrimethylammonium bromide, dodecyltrimethylammonium bromide, sodium dodecyl sulfate, sodium dodecyl sulfonate, and dodecyltrimethylammonium bromide; and the mass ratio of the surfactant to the conductive carbon carrier is 1 to 10:1.
[0018] Preferably, in step (1), the volume ratio of ethanol to ultrapure water is 1:9, and the concentration of the carbon carrier suspension is 1-10 mg / mL.
[0019] Preferably, in the step (2), the alkaline solution is one of sodium hydroxide solution, potassium hydroxide solution, calcium hydroxide solution, and ammonia water, the mass ratio of the alkali in the alkaline solution to the conductive carbon carrier is 1 to 20:1, and the amount of the rare earth metal precursor solution added is calculated according to the mass ratio of the rare earth oxide to the conductive carbon carrier satisfying 3:7; in the step (4), the molar concentration ratio of the platinum precursor solution to the transition metal precursor solution is 0.5 to 10:1, and the platinum concentration in the mixture slurry is 0.5 to 10 mg / mL. Platinum salt precursors mainly include platinum dichloride, potassium chloroplatinate, platinum tetrachloride, sodium hexachloroplatinate, chloroplatinic acid, platinum acetylacetonate, etc. Transition metal precursors mainly include nickel chloride hexahydrate, nickel acetylacetonate, nickel acetate, cobalt chloride hexahydrate, cobalt acetylacetonate, cobalt acetate, ferric chloride hexahydrate, ferric acetylacetonate or ferric acetate, ruthenium acetylacetonate, ruthenium acetate, ruthenium chloride, ruthenium iodide, etc. The platinum precursor solution and the transition metal precursor solution are prepared by dissolving a platinum salt precursor and a transition metal precursor in a solvent.
[0020] Preferably, the hydrothermal reaction temperature is 160°C, the hydrothermal reaction time is 2h, and after the hydrothermal reaction, the reaction product is filtered, washed, and vacuum dried in sequence; in the step (5), the hydrothermal reaction temperature is 100-200°C, the hydrothermal reaction time is 1-30h, and after the hydrothermal reaction, the reaction product is filtered, washed, vacuum dried, and acid washed in sequence. After the acid wash is completed, the reaction product is filtered, washed, and vacuum dried again. The hydrogen reduction heat treatment temperature is 250-900°C, the heat treatment time is 0.5-6h, and after the heat treatment is completed, the heat treatment product is acid washed, filtered, washed, and vacuum dried in sequence. During the hydrogen reduction heat treatment process, the gas introduced is a mixed gas of hydrogen and nitrogen or hydrogen and argon. When the mixed gas is hydrogen and nitrogen, the volume ratio of nitrogen to hydrogen in the mixed gas is 3 to 12:1. When the mixed gas is hydrogen and argon, the volume ratio of argon to hydrogen in the mixed gas is 5 to 15:1. The flow rate of the mixed gas is
[0021] 30~1200mL / min.
[0022] The present invention also provides a high compressive strain platinum alloy nano material, and the high compressive strain platinum alloy nano material is prepared according to the above preparation method.
[0023] The present invention further proposes an application of a high compressive strain platinum alloy nanomaterial in hydrogen-oxygen fuel cells and methanol fuel cells.
[0024] Among various rare earth metal elements, rare earth metal elements that are prone to losing their outermost orbital electrons, such as cerium (Ce) ([Xe]4f15d16s2), praseodymium (Pr) ([Xe]4f36s2), and terbium (Tb) ([Xe]4f96s2), form compounds with other non-metallic elements. Rare earth metal ions will show a conversion between +3 and +4 valence. Some rare earth elements also show a transition between +2 and +3 valence when forming compounds with other non-metallic elements (e.g. ). As a result, in the process of rare earth elements exchanging electrons with oxygen to form rare earth oxides, a defect structure in which high-valent and low-valent oxides coexist will be formed, causing the oxidation state of the rare earth metal ions in the oxide to switch between high-valent and low-valent states. Taking CeO2 as an example, the oxidation state of its Ce ions is between Ce 3+ and Ce 4+ The characteristic of rare earth oxides enables them to significantly promote the rate of redox reactions. Accordingly, in the process of in-situ reduction nucleation and growth of Pt ions and transition metal M ions on rare earth oxide nanoparticles / carbon carrier composites to form PtM alloy nanoparticles, the rare earth metal ions in the rare earth oxides will be reduced to low-valent oxides. When there are too many low-valent rare earth metal ions, the low-valent rare earth metal ions will be converted to high-valent rare earth metal ions. In this process, Pt with higher electronegativity obtains electrons given by low-valent rare earth metal ions, thereby increasing the negative charge density around Pt ions, reducing the gap between the reduction potential of Pt and the reduction potential of transition metal M, and reducing the gap between the reduction rate of Pt and the reduction rate of transition metals. This allows Pt ions to form metal bonds with more positively charged transition metal ions during the nucleation and growth process, so that more transition metal atoms with smaller atomic radius than Pt are incorporated into the Pt alloy, thereby reducing the Pt lattice constant, generating high compressive strain, and promoting the improvement of the catalytic activity of the Pt alloy. In addition, the corrosion-resistant rare earth oxide protective layer formed on the surface of the carbon support can inhibit the electrical corrosion of the carbon support under potential and improve the structural stability of the Pt alloy nanomaterials.
[0025] Beneficial effects of the present invention:
[0026] 1. The present invention forms PtM alloy nanoparticles by in-situ reduction nucleation and growth of Pt ions and transition metal ions on a carbon carrier / rare earth oxide nanoparticle composite, and utilizes the catalytic effect of rare earth oxides to induce more transition metals to be incorporated into the Pt lattice, thereby reducing the Pt lattice constant, generating high compressive strain, and promoting the catalytic effect of platinum alloy nanomaterials.
[0027] 2. The present invention forms a rare earth oxide layer by uniformly depositing rare earth oxide nanoparticles on the surface of a conductive carbon carrier. Since rare earth oxides have good corrosion resistance under acidic or alkaline conditions, they can protect the conductive carbon carrier, inhibit the degree of electrical corrosion of the conductive carbon carrier during high-potential operation of the fuel cell, reduce the risk of structural collapse of the conductive carbon carrier, and enhance the structural stability of the platinum alloy nanomaterial.
[0028] 3. After the rare earth oxide nanoparticles are uniformly deposited on the surface of the conductive carbon carrier, the Pt ions and transition metal ions are in situ reduced to nucleate and grow on the rare earth oxide layer to form PtM alloy nanoparticles, which is equivalent to the PtM alloy nanoparticles being located in the outermost layer of the platinum alloy nanomaterial, which can ensure that they are not blocked by the rare earth oxide layer during use and are in full contact with other substances to play a catalytic role in the reaction.
[0029] 4. The Pt alloy nanoparticles of the present invention are formed by in-situ reduction nucleation on the rare earth oxide layer. The interaction between the Pt alloy nanoparticles and the rare earth oxides is strong. The rare earth oxides can prevent the Pt alloy nanoparticles from agglomerating, dissolving, and falling off during long-term operation at low potential in the fuel cell, thereby improving the durability of the platinum alloy nanomaterial. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 The X-ray diffraction (XRD) pattern of the cerium dioxide / carbon support composite.
[0031] Figure 2 This is a transmission electron microscope (TEM) image of the cerium dioxide / carbon support composite.
[0032] Figure 3 This is the TEM image of the platinum alloy nanomaterial prepared in Example 1.
[0033] Figure 4 This is the TEM image of the platinum alloy nanomaterial prepared in Example 2.
[0034] Figure 5 1 is a comparison diagram of the high-resolution X-ray photoelectron spectroscopy (XPS) of Pt 4f of Example 2 and Comparative Example 2.
[0035] Figure 6 The XRD diagrams of platinum alloy nanomaterials prepared in Example 1 and Comparative Example 1 are shown.
[0036] Figure 7 The XRD diagrams of platinum alloy nanomaterials prepared in Example 2 and Comparative Example 2 are shown.
[0037] Figure 8It is a comparative bar graph of the electrochemical areas of cyclic voltammetry (CV) tests of Examples 1-3 and Comparative Examples 1-3 in a 0.1M HClO4 solution saturated with N2.
[0038] Fig. 9 It is a comparative bar graph of the oxygen reduction (ORR) mass activity of Examples 1-3 and Comparative Examples 1-3 in a 0.1M HClO4 solution saturated with O2 using linear sweep voltammetry (LSV).
[0039] Fig.10 It is a comparative bar graph of the methanol oxidation (MOR) mass activity of the examples and comparative examples in 0.1M HClO4+1M CH3OH solution.
[0040] Fig.11 This is a comparison chart of the mass (ORR) activity loss rate test results of Example 1-3 and Comparative Example 1-3 after 30,000 cycles (0.6-0.95 V) in a 0.1 M HClO4 solution saturated with N2.
[0041] Fig.12 This is a comparison chart of the mass (ORR) activity loss rate test results of Example 1-3 and Comparative Example 1-3 after 5000 cycles (1.0-1.5V) in a 0.1M HClO4 solution saturated with N2.
[0042] Fig.13 This is a schematic diagram of the material morphology changes during the preparation process of the platinum alloy nanomaterial of the present invention. DETAILED DESCRIPTION
[0043] The present invention is further described in detail below in conjunction with specific embodiments.
[0044] In the examples and comparative examples of the present invention, chemical reagents not otherwise specified were all commercially available analytically pure reagents for the experiments.
[0045] Example 1
[0046] This example prepares platinum alloy nanomaterials according to the following method:
[0047] (1) EC-300J (conductive carbon carrier), citric acid (morphology control agent), and hexadecyltrimethylammonium bromide (surfactant) were added to an ethanol-ultrapure water mixed liquid (the volume ratio of ethanol to ultrapure water was 1:9), and ultrasonic treatment was performed for 30 minutes to obtain an EC-300J suspension. The mass ratio of citric acid to EC-300J was 4:1, and the mass ratio of hexadecyltrimethylammonium bromide to EC-300J was 2:1.
[0048] (2) Adding cerium nitrate solution to the EC-300J suspension under strong stirring and ultrasonication for 1 hour, and then adding 0.5 mol / L NaOH solution to obtain a mixed solution. The amount of cerium nitrate solution added is calculated based on the theoretical mass ratio of cerium dioxide to EC-300J in the carbon support / cerium dioxide nanoparticle composite of 3:7, and the mass ratio of NaOH to EC-300J in the NaOH solution is 10:1.
[0049] (3) The mixed solution was ultrasonically treated for 30 min and then stirred for 30 min. The mixed solution was then transferred to a high-pressure reactor and subjected to a hydrothermal reaction at 160° C. for 2 h. The mixture was cooled to room temperature and the reaction product was filtered to obtain a solid substance. The solid substance was washed with an ethanol-deionized water mixture until it was neutral and dried in vacuo to obtain a carbon carrier / cerium dioxide nanoparticle composite.
[0050] The cerium dioxide nanoparticle / carbon carrier composite prepared in this example was subjected to X-ray diffraction and transmission electron microscopy experiments, and the results were as follows: Figure 1 , 2 shown.
[0051] (4) The carbon support / cerium dioxide nanoparticle composite, platinum acetylacetonate (platinum precursor) and nickel acetylacetonate (transition metal precursor) were mixed and added to ethylene glycol (solvent), and stirred for 30 minutes after ultrasonic treatment for 1 hour to obtain a mixture slurry. In the mixture slurry, the concentration of Pt was 0.5 mg / ml, the atomic ratio of Pt to Ni was 1:1, and the mass ratio of Pt to EC-300J was 0.25.
[0052] (5) The mixture slurry is placed in a high-pressure reactor and reduced at 200°C for 6 hours. After the reaction is completed, the reaction product is filtered to obtain a solid substance, and the solid substance is washed with a mixed liquid of water and ethanol, and vacuum dried to obtain a powder. The powder is added to an 8.75 mol / L acetic acid solution and stirred and acid washed at 60°C for 2 hours. After completion, the liquid is removed by suction filtration, and the solid substance is washed with a mixed liquid of water and ethanol. After vacuum drying, a platinum alloy nanomaterial is obtained, which is recorded as PtNi-CeO2 / C.
[0053] The platinum alloy nanomaterial prepared in this example was subjected to transmission electron microscopy experiments, and the results are as follows: Figure 3 shown.
[0054] The X-ray diffraction experiment was carried out on the platinum alloy nanomaterial prepared in this example, and the results are as follows: Figure 6 shown.
[0055] Example 2
[0056] This example prepares platinum alloy nanomaterials according to the following method:
[0057] (1) Add acetylene black (conductive carbon carrier), sodium citrate (morphology control agent), and sodium hexadecyl sulfate (surfactant) into an ethanol-ultrapure water mixed liquid (the volume ratio of ethanol to ultrapure water is 1:9), and ultrasonically treat for 30 minutes to obtain an acetylene black suspension. The mass ratio of sodium citrate to acetylene black is 4:1, and the mass ratio of sodium hexadecyl sulfate to acetylene black is 2:1.
[0058] (2) adding cerium sulfate solution to the acetylene black suspension under strong stirring and ultrasonicating for 1 hour, and then adding 0.5 mol / L NaOH solution to obtain a mixed solution. The amount of cerium sulfate solution added is calculated according to the theoretical mass ratio of cerium dioxide to acetylene black in the cerium dioxide nanoparticle / carbon support composite of 3:7, and the mass ratio of NaOH to acetylene black in the NaOH solution is 10:1.
[0059] (3) The mixed solution was ultrasonically treated for 30 min and then stirred for 30 min. The mixed solution was then transferred to a high-pressure reactor and subjected to a hydrothermal reaction at 160° C. for 2 h. The mixture was cooled to room temperature and the reaction product was filtered to obtain a solid substance. The solid substance was washed with an ethanol-deionized water mixture until it was neutral and dried in vacuo to obtain a carbon carrier / cerium dioxide nanoparticle composite.
[0060] (4) The carbon support / cerium dioxide nanoparticle composite, platinum dichloride (platinum precursor) and cobalt acetate (transition metal precursor) were mixed and added to ethylene glycol (solvent), and stirred for 30 minutes after ultrasonic treatment for 1 hour to obtain a mixture slurry. In the mixture slurry, the concentration of Pt was 0.5 mg / ml, the atomic ratio of Pt to Co was 1:1, and the mass ratio of Pt to acetylene black was 0.25.
[0061] (5) The mixture slurry is placed in a round-bottom flask, and the round-bottom flask is placed in an oil bath, and the mixture is reduced by stirring at 200°C for 6 hours. After the reaction is completed, the reaction product is filtered to obtain a solid substance, and the solid substance is washed with a mixed liquid of water and ethanol, and vacuum dried to obtain a powder. The powder is added to an 8.75 mol / L acetic acid solution, stirred and acid washed at 60°C for 2 hours. After completion, the liquid is removed by suction filtration, and the solid substance is washed with a mixed liquid of water and ethanol, and vacuum dried to obtain a platinum alloy nanomaterial, which is recorded as PtCo-CeO2 / C.
[0062] The platinum alloy nanomaterial prepared in this example was subjected to transmission electron microscopy experiments, and the results are as follows: Figure 4 shown.
[0063] The X-ray photoelectron spectroscopy experiment was performed on the platinum alloy nanomaterial prepared in this example. The results are as follows: Figure 5 shown.
[0064] The X-ray diffraction experiment was carried out on the platinum alloy nanomaterial prepared in this example, and the results are as follows: Figure 7 shown.
[0065] Example 3
[0066] This example prepares platinum alloy nanomaterials according to the following method:
[0067] (1) BP-2000 (conductive carbon carrier), potassium citrate (morphology control agent), and octadecyltrimethylammonium bromide (surfactant) were added to an ethanol-ultrapure water mixed liquid (the volume ratio of ethanol to ultrapure water was 1:9), and ultrasonically treated for 30 minutes to obtain a BP-2000 suspension. The mass ratio of potassium citrate to BP-2000 was 4:1, and the mass ratio of octadecyltrimethylammonium bromide to BP-2000 was 2:1.
[0068] (2) Adding terbium chloride solution to the BP-2000 suspension under strong stirring and ultrasonication for 1 hour, and then adding 0.5 mol / L NaOH solution to obtain a mixed solution. The amount of terbium chloride solution added is calculated based on the theoretical mass ratio of terbium dioxide to BP-2000 in the carbon support / terbium dioxide nanoparticle composite of 3:7, and the mass ratio of NaOH to BP-2000 in the NaOH solution is 10:1.
[0069] (3) The mixed solution was ultrasonically treated for 30 minutes and then stirred for 30 minutes. The mixed solution was then transferred to a high-pressure reactor and subjected to a hydrothermal reaction at 160° C. for 2 hours. The mixed solution was cooled to room temperature and the reaction product was filtered to obtain a solid substance. The solid substance was washed with an ethanol-deionized water mixture until it was neutral and dried in vacuo to obtain a carbon carrier / terbium dioxide nanoparticle composite.
[0070] (4) The carbon support / terbium dioxide nanoparticle composite, platinum tetrachloride (platinum precursor) and ferric chloride hexahydrate (transition metal precursor) were mixed and added to acetone (solvent), and stirred for 30 minutes after ultrasonic treatment for 1 hour to obtain a mixture slurry. In the mixture slurry, the concentration of Pt was 0.5 mg / ml, the atomic ratio of Pt to Fe was 1:1, and the mass ratio of Pt to BP-2000 was 0.25.
[0071] (5) The mixture slurry is placed in a water bath, stirred at 60°C to evaporate acetone to obtain solid powder, the solid powder is placed in a tube furnace, a mixed gas of argon and hydrogen with a volume ratio of 4:1 is introduced, and calcined at 580°C for 4 hours to obtain powder after reaction. The powder is added to 8.75 mol / L acetic acid solution, stirred at 60°C for acid washing for 2 hours, and then filtered to remove the liquid, and the solid matter is washed with a mixed liquid of water and ethanol, and vacuum dried to obtain a platinum alloy nanomaterial, which is recorded as PtFe-TbO2 / C.
[0072] Example 4
[0073] This example prepares platinum alloy nanomaterials according to the following method:
[0074] (1) XC-72 (conductive carbon carrier), calcium citrate (morphology control agent), and tetradecyltrimethylammonium bromide (surfactant) were added to an ethanol-ultrapure water mixed liquid (the volume ratio of ethanol to ultrapure water was 1:9), and ultrasonic treatment was performed for 30 minutes to obtain an XC-72 suspension. The mass ratio of calcium citrate to XC-72 was 4:1, and the mass ratio of tetradecyltrimethylammonium bromide to XC-72 was 2:1.
[0075] (2) Adding europium nitrate solution to the XC-72 suspension under strong stirring and ultrasonication for 1 hour, and then adding 0.5 mol / L NaOH solution to obtain a mixed solution. The amount of europium nitrate solution added is calculated according to the theoretical mass ratio of europium trioxide to XC-72 in the europium trioxide nanoparticle composite of 3:7, and the mass ratio of NaOH to XC-72 in the NaOH solution is 10:1.
[0076] (3) The mixed solution was ultrasonically treated for 30 minutes and then stirred for 30 minutes. The mixed solution was then transferred to a high-pressure reactor and subjected to a hydrothermal reaction at 160° C. for 2 hours. The mixture was cooled to room temperature and the reaction product was filtered to obtain a solid substance. The solid substance was washed with an ethanol-deionized water mixture until it was neutral and dried in vacuo to obtain a carbon carrier / europium trioxide nanoparticle composite.
[0077] (4) The carbon support / Europium trioxide nanoparticle composite, chloroplatinic acid (platinum precursor) and ruthenium acetylacetonate (transition metal precursor) were mixed and added to acetone (solvent), and stirred for 30 minutes after ultrasonic treatment for 1 hour to obtain a mixture slurry. In the mixture slurry, the concentration of Pt was 0.5 mg / ml, the atomic ratio of Pt to Ru was 1:1, and the mass ratio of Pt to XC-72 was 0.25.
[0078] (5) The mixture slurry is placed in a water bath, stirred at 60°C to evaporate acetone to obtain solid powder, the solid powder is placed in a tube furnace, a mixed gas of argon and hydrogen with a volume ratio of 4:1 is introduced, and calcined at 580°C for 4 hours to obtain powder after reaction. The powder is added to 8.75 mol / L acetic acid solution, stirred at 60°C for acid washing for 2 hours, and then filtered to remove the liquid, and the solid matter is washed with a mixed liquid of water and ethanol, and vacuum dried to obtain a platinum alloy nanomaterial, which is recorded as PtRu-Eu2O3 / C.
[0079] Example 5
[0080] This example prepares platinum alloy nanomaterials according to the following method:
[0081] (1) EC-300J (conductive carbon support), citric acid (morphology control agent), and hexadecyltrimethylammonium bromide (surfactant) were added to an ethanol-ultrapure water mixed liquid (the volume ratio of ethanol to ultrapure water was 1:9), and ultrasonic treatment was performed for 30 minutes to obtain an EC-300J suspension. The mass ratio of citric acid to EC-300J was 1:1, and the mass ratio of hexadecyltrimethylammonium bromide to EC-300J was 1:1.
[0082] (2) Adding cerium nitrate solution to the EC-300J suspension under strong stirring and ultrasonication for 1 hour, and then adding 0.5 mol / L NaOH solution to obtain a mixed solution. The amount of cerium nitrate solution added is calculated based on the theoretical mass ratio of cerium dioxide to EC-300J in the carbon support / cerium dioxide nanoparticle composite of 3:7, and the mass ratio of NaOH to EC-300J in the NaOH solution is 1:1.
[0083] (3) The mixed solution was ultrasonically treated for 30 min and then stirred for 30 min. The mixed solution was then transferred to a high-pressure reactor and subjected to a hydrothermal reaction at 160° C. for 2 h. The mixture was cooled to room temperature and the reaction product was filtered to obtain a solid substance. The solid substance was washed with an ethanol-deionized water mixture until it was neutral and dried in vacuo to obtain a carbon carrier / cerium dioxide nanoparticle composite.
[0084] (4) The carbon support / cerium dioxide nanoparticle composite, platinum acetylacetonate (platinum precursor) and nickel acetylacetonate (transition metal precursor) were mixed and added to ethylene glycol (solvent), and stirred for 30 minutes after ultrasonic treatment for 1 hour to obtain a mixture slurry. In the mixture slurry, the concentration of Pt was 10 mg / ml, the atomic ratio of Pt to Ni was 0.5:1, and the mass ratio of Pt to EC-300J was 0.25.
[0085] (5) The mixture slurry is placed in a high-pressure reactor, and after the reaction is completed at 100°C for 30 hours, the reaction product is filtered to obtain a solid substance, and the solid substance is washed with a mixed liquid of water and ethanol, and vacuum dried to obtain a powder. The powder is added to an 8.75 mol / L acetic acid solution, stirred and acid washed at 60°C for 2 hours, and after completion, the liquid is removed by suction filtration, and the solid substance is washed with a mixed liquid of water and ethanol, and vacuum dried to obtain a platinum alloy nanomaterial.
[0086] The platinum alloy nanomaterial prepared in this example has similar performance to that of Example 1.
[0087] Example 6
[0088] This example prepares platinum alloy nanomaterials according to the following method:
[0089] (1) EC-300J (conductive carbon support), citric acid (morphology control agent), and hexadecyltrimethylammonium bromide (surfactant) were added to an ethanol-ultrapure water mixed liquid (the volume ratio of ethanol to ultrapure water was 1:9), and ultrasonic treatment was performed for 30 minutes to obtain an EC-300J suspension. The mass ratio of citric acid to EC-300J was 10:1, and the mass ratio of hexadecyltrimethylammonium bromide to EC-300J was 10:1.
[0090] (2) Adding cerium nitrate solution to the EC-300J suspension under strong stirring and ultrasonication for 1 hour, and then adding 0.5 mol / L NaOH solution to obtain a mixed solution. The amount of cerium nitrate solution added is calculated based on the theoretical mass ratio of cerium dioxide to EC-300J in the carbon support / cerium dioxide nanoparticle composite of 3:7, and the mass ratio of NaOH to EC-300J in the NaOH solution is 20:1.
[0091] (3) The mixed solution was ultrasonically treated for 30 min and then stirred for 30 min. The mixed solution was then transferred to a high-pressure reactor and subjected to a hydrothermal reaction at 160° C. for 2 h. The mixture was cooled to room temperature and the reaction product was filtered to obtain a solid substance. The solid substance was washed with an ethanol-deionized water mixture until it was neutral and dried in vacuo to obtain a carbon carrier / cerium dioxide nanoparticle composite.
[0092] (4) The carbon support / cerium dioxide nanoparticle composite, platinum acetylacetonate (platinum precursor) and nickel acetylacetonate (transition metal precursor) were mixed and added to ethylene glycol (solvent), and stirred for 30 minutes after ultrasonic treatment for 1 hour to obtain a mixture slurry. In the mixture slurry, the concentration of Pt was 5 mg / ml, the atomic ratio of Pt to Ni was 10:1, and the mass ratio of Pt to EC-300J was 0.25.
[0093] (5) The mixture slurry is placed in a high-pressure reactor, reduced at 150°C for 1 hour, washed with a mixed liquid of water and ethanol, and vacuum dried to obtain a powder. The powder is added to an 8.75 mol / L acetic acid solution, stirred and acid washed at 60°C for 2 hours, and after completion, the liquid is removed by suction filtration, the solid matter is washed with a mixed liquid of water and ethanol, and vacuum dried to obtain a platinum alloy nanomaterial.
[0094] The platinum alloy nanomaterial prepared in this example has similar performance to that of Example 1.
[0095] Example 7
[0096] This example prepares platinum alloy nanomaterials according to the following method:
[0097] (1) BP-2000 (conductive carbon carrier), potassium citrate (morphology control agent), and octadecyltrimethylammonium bromide (surfactant) were added to an ethanol-ultrapure water mixed liquid (the volume ratio of ethanol to ultrapure water was 1:9), and ultrasonically treated for 30 minutes to obtain a BP-2000 suspension. The mass ratio of potassium citrate to BP-2000 was 1:1, and the mass ratio of octadecyltrimethylammonium bromide to BP-2000 was 1:1.
[0098] (2) Adding terbium chloride solution to the BP-2000 suspension under strong stirring and ultrasonication for 1 hour, and then adding 0.5 mol / L NaOH solution to obtain a mixed solution. The amount of terbium chloride solution added is calculated according to the theoretical mass ratio of terbium dioxide to BP-2000 in the carbon support / terbium dioxide nanoparticle composite of 3:7, and the mass ratio of NaOH to BP-2000 in the NaOH solution is 1:1.
[0099] (3) The mixed solution was ultrasonically treated for 30 minutes and then stirred for 30 minutes. The mixed solution was then transferred to a high-pressure reactor and subjected to a hydrothermal reaction at 160° C. for 2 hours. The mixed solution was cooled to room temperature and the reaction product was filtered to obtain a solid substance. The solid substance was washed with an ethanol-deionized water mixture until it was neutral and dried in vacuo to obtain a carbon carrier / terbium dioxide nanoparticle composite.
[0100] (4) The carbon support / terbium dioxide nanoparticle composite, platinum tetrachloride (platinum precursor) and ferric chloride hexahydrate (transition metal precursor) were mixed and added to acetone (solvent), and stirred for 30 minutes after ultrasonic treatment for 1 hour to obtain a mixture slurry. In the mixture slurry, the concentration of Pt was 10 mg / ml, the atomic ratio of Pt to Fe was 0.5:1, and the mass ratio of Pt to BP-2000 was 0.25.
[0101] (5) The mixture slurry is placed in a water bath, and the acetone is evaporated with stirring at 60°C to obtain a solid powder. The solid powder is placed in a tube furnace, and a mixed gas of argon and hydrogen with a volume ratio of 4:1 is introduced, and calcined at 250°C for 6 hours to obtain a powder after the reaction. The powder is added to an 8.75 mol / L acetic acid solution, stirred and acid-washed at 60°C for 2 hours. After completion, the liquid is removed by suction filtration, and the solid matter is washed with a mixed liquid of water and ethanol, and the platinum alloy nanomaterial is obtained after vacuum drying.
[0102] The platinum alloy nanomaterial prepared in this example has similar performance to that of Example 3.
[0103] Example 8
[0104] This example prepares platinum alloy nanomaterials according to the following method:
[0105] (1) BP-2000 (conductive carbon carrier), potassium citrate (morphology control agent), and octadecyltrimethylammonium bromide (surfactant) were added to an ethanol-ultrapure water mixed liquid (the volume ratio of ethanol to ultrapure water was 1:9), and ultrasonically treated for 30 minutes to obtain a BP-2000 suspension. The mass ratio of potassium citrate to BP-2000 was 10:1, and the mass ratio of octadecyltrimethylammonium bromide to BP-2000 was 10:1.
[0106] (2) Adding terbium chloride solution to the BP-2000 suspension under strong stirring and ultrasonication for 1 hour, and then adding 0.5 mol / L NaOH solution to obtain a mixed solution. The amount of terbium chloride solution added is calculated based on the theoretical mass ratio of terbium dioxide to BP-2000 in the carbon support / terbium dioxide nanoparticle composite of 3:7, and the mass ratio of NaOH to BP-2000 in the NaOH solution is 20:1.
[0107] (3) The mixed solution was ultrasonically treated for 30 minutes and then stirred for 30 minutes. The mixed solution was then transferred to a high-pressure reactor and subjected to a hydrothermal reaction at 160° C. for 2 hours. The mixed solution was cooled to room temperature and the reaction product was filtered to obtain a solid substance. The solid substance was washed with an ethanol-deionized water mixture until it was neutral and dried in vacuo to obtain a carbon carrier / terbium dioxide nanoparticle composite.
[0108] (4) The carbon support / terbium dioxide nanoparticle composite, platinum tetrachloride (platinum precursor) and ferric chloride hexahydrate (transition metal precursor) were mixed and added to acetone (solvent), and stirred for 30 minutes after ultrasonic treatment for 1 hour to obtain a mixture slurry. In the mixture slurry, the concentration of Pt was 5 mg / ml, the atomic ratio of Pt to Fe was 10:1, and the mass ratio of Pt to BP-2000 was 0.25.
[0109] (5) The mixture slurry is placed in a water bath, and the acetone is evaporated with stirring at 60°C to obtain a solid powder. The solid powder is placed in a tube furnace, and a mixed gas of argon and hydrogen with a volume ratio of 4:1 is introduced, and calcined at 900°C for 0.5h to obtain a powder after the reaction. The powder is added to an 8.75mol / L acetic acid solution, stirred and acid-washed at 60°C for 2h. After completion, the liquid is removed by suction filtration, and the solid matter is washed with a mixed liquid of water and ethanol, and the platinum alloy nanomaterial is obtained after vacuum drying.
[0110] The platinum alloy nanomaterial prepared in this example has similar performance to that of Example 3.
[0111] Comparative Example 1:
[0112] This comparative example adopts the same method as Example 1 to prepare platinum alloy nanomaterials, except that: no rare earth metal precursor solution is added in this comparative example.
[0113] The platinum alloy nanomaterial prepared in this comparative example is denoted as PtNi / C.
[0114] Comparative Example 2:
[0115] This comparative example adopts the same method as Example 2 to prepare platinum alloy nanomaterials, except that: no rare earth metal precursor solution is added in this comparative example.
[0116] The platinum alloy nanomaterial prepared in this comparative example is denoted as PtCo / C.
[0117] Comparative Example 3:
[0118] This comparative example adopts the same method as Example 3 to prepare platinum alloy nanomaterials, except that: no rare earth metal precursor solution is added in this comparative example.
[0119] The platinum alloy nanomaterial prepared in this comparative example is denoted as PtFe / C.
[0120] Comparative Example 4:
[0121] This comparative example adopts the same method as Example 4 to prepare platinum alloy nanomaterials, except that: no rare earth metal precursor solution is added in this comparative example.
[0122] The platinum alloy nanomaterial prepared in this comparative example is denoted as PtRu / C.
[0123] The platinum alloy nanomaterials prepared in the examples and comparative examples were subjected to catalytic performance experiments, and the results were as follows: Figure 8-12 shown.
[0124] pass Figure 1 It can be seen that each diffraction peak in the XRD pattern of the ceria nanoparticle / carbon support composite corresponds to the standard FDF card of ceria, indicating that the phase of the sample is ceria. Figure 2 It can be seen that the nanoparticles with an average size of about 3.46 nm are uniformly dispersed on the surface of the carbon carrier. These results show that the cerium dioxide nanoparticle / carbon carrier composite prepared in Example 1 is composed of cerium dioxide nanoparticles with an average size of about 3.46 nm uniformly dispersed on the surface of the carbon carrier. This shows that the present invention can achieve the effect of depositing rare earth oxide nanoparticles on the surface of the conductive carbon carrier to form a rare earth oxide layer.
[0125] pass Figure 3It can be seen that PtNi alloy nanoparticles are dispersed on the surface of ceria nanoparticles, and many of them are in contact or overlap with ceria nanoparticles. On the one hand, it shows that the rare earth oxide layer will not block the Pt alloy nanoparticles, and on the other hand, it can be confirmed that rare earth oxides can prevent Pt alloy nanoparticles from agglomerating, dissolving, and falling off during long-term operation at low potential in fuel cells, thereby improving the durability of platinum alloy nanomaterials.
[0126] pass Figure 4 It can be seen that in the PtCo-CeO2 / C alloy nanomaterial, PtCo alloy nanoparticles are dispersed on the surface of cerium dioxide nanoparticles, and many PtCo alloy nanoparticles are in contact or overlapped with cerium dioxide nanoparticles, indicating that the platinum alloy nanomaterial prepared in Example 2 has similar properties to that of Example 1.
[0127] pass Figure 5 It can be seen that the Pt 4f peak of Example 2 shifts to the left compared with the Pt 4f peak of Comparative Example 2, indicating that the binding energy of Pt in Example 2 is reduced, which means that the electron transfer effect of the rare earth metal oxide reduces the binding energy of Pt, inducing more transition metals with small atomic radius to be integrated into the platinum alloy, resulting in a decrease in the platinum lattice constant and high compressive strain.
[0128] pass Figure 6 , Figure 7 It can be seen that the platinum alloy nanomaterials prepared in Example 1 and Example 2 contain CeO2 and Pt phases, but no Ni and Co phases, indicating that all transition metals are integrated into the Pt lattice to form a platinum alloy. In Comparative Examples 1 and 2, since there is no CeO2 phase, the peak angle of Pt is lower, proving that the degree of alloying is lower than that with CeO2.
[0129] According to the Bragg formula 2dSinθ=λ (d-interplanar spacing, θ-diffraction angle, λ-X-ray wavelength), the interplanar spacing of the Pt(111) crystal plane is calculated. According to the formula a=d(h 2 +k 2 +l 2 ) 1 / 2 The Pt(hkl) crystal plane index is used to calculate the lattice constant of Pt from the interplanar spacing of the (111) crystal plane. The results are shown in Table 1. The designed nominal atomic ratio of Pt to transition metal M in the Pt alloy nanomaterials prepared in the embodiments and comparative examples is 1:1. Taking the embodiment 1 and comparative example 1 as examples, by Figure 6It can be seen that the XRD diffraction peak positions of PtNi / C prepared in Comparative Example 1 are approximately at 39.863°, 46.145°, 67.888° and 81.827°, and the positions of these diffraction peaks correspond to the diffraction peak positions of (111), (200), (220) and (311) crystal planes of the face-centered cubic (fcc) structure of Pt metal (JCPDS04-0802). The XRD diffraction peak positions of PtNi-CeO2 / C prepared in Example 1 are approximately at 40.195°, 46.813°, 68.321° and 82.32°, and the positions of these diffraction peaks correspond to the diffraction peak positions of (111), (200), (220) and (311) crystal planes of the face-centered cubic (fcc) structure of Pt metal (JCPDS04-0802). By comparison, it can be seen that the CeO2 / C complex causes the position of the Pt diffraction peak to shift significantly to a higher angle. The position of the Pt diffraction peak increases. According to the Bragg formula 2dSinθ=λ, the interplanar spacing and lattice constant of the Pt(111) crystal plane in Comparative Example 1 are 0.2241nm and 0.3881nm, respectively, while the interplanar spacing and lattice constant of the Pt(111) crystal plane in Example 1 are 0.2250nm and 0.3897nm, respectively. The interplanar spacing and lattice constant of the Pt(111) crystal plane in Comparative Example 1 are significantly larger than those of the Pt(111) crystal plane in Example 1. This result shows that CeO2 induces the contraction of the Pt lattice spacing and the decrease of the lattice constant in the PtNi alloy.
[0130] Table 1
[0131] (111) interplanar spacing d (nm) Lattice constant a(nm) Pt:M (atomic ratio) Example 1 0.2241 0.3881 Pt:Ni=1:0.32 Comparative Example 1 0.2250 0.3897 Pt:Ni=1:0.21 Example 2 0.2162 0.3744 Pt:Co=1:0.31 Comparative Example 2 0.2169 0.3756 Pt:Co=1:0.22 Example 3 0.2243 0.3884 Pt:Fe=1:0.27 Comparative Example 3 0.2250 0.3897 Pt:Fe=1:0.19 Example 4 0.2149 0.3722 Pt:Ru=1:0.20 Comparative Example 4 0.2154 0.3730 Pt:Ru=1:0.13
[0132] It can be seen from Table 1 that the interplanar spacing and lattice constant of the Pt(111) crystal plane in the embodiment of the present invention are both smaller than those of the Pt(111) crystal plane in Comparative Example 1, which indicates that the rare earth oxide successfully induces the Pt lattice spacing in the platinum alloy to shrink and the lattice constant to decrease. The platinum alloy nanomaterial prepared by the present invention can generate high compressive strain and effectively promote the catalytic effect of the platinum alloy nanomaterial.
[0133] EDS was used to test the atomic ratio of platinum to transition metal in the embodiments and comparative examples, as shown in Table 1. It can be seen from Table 1 that in the embodiments and comparative examples, the atomic ratio of transition metal is lower than the designed nominal atomic ratio. This is because the unalloyed transition metal is removed during the pickling process. However, the atomic ratio of transition metal in the embodiments is significantly higher than that in the comparative example, indicating that rare earth oxides can successfully induce more transition metals to enter the Pt lattice.
[0134] pass Figure 8-12The quantitative data can be obtained as shown in Tables 2-3. Table 2 shows the test results of the oxygen reduction catalytic performance of the Pt alloy nanomaterials prepared in Examples 1-3 and Comparative Examples 1-3, and Table 3 shows the test results of the methanol oxidation catalytic performance of the Pt alloy nanomaterials prepared in Examples and Comparative Examples.
[0135] Table 2
[0136]
[0137] According to Table 2, combined Figure 8 , 9 , 11, and 12, it can be seen that the platinum alloy nanomaterial prepared by the present invention not only has a larger electrochemical active area and a higher oxygen reduction catalytic mass activity, but also has a significantly reduced loss rate, indicating that the platinum alloy nanomaterial prepared by the present invention has better comprehensive catalytic performance.
[0138] Table 3
[0139]
[0140]
[0141] According to Table 3, combined Fig.10 It can be seen that the platinum alloy nanomaterial prepared in the present invention has higher methanol oxidation catalytic mass activity under acidic conditions.
[0142] In summary, the platinum alloy nanomaterial of the present invention can form metal bonds with more positively charged transition metal ions during the nucleation and growth process through the electron transfer effect between nano rare earth oxide and Pt ions, so that more transition metal atoms with smaller atomic radius than platinum are incorporated into the Pt alloy, thereby preparing a Pt alloy nanomaterial with high Pt alloying degree and high compressive strain, and significantly improving the catalytic performance of the Pt alloy nanomaterial. Secondly, the strong interaction between the rare earth oxide and the Pt alloy nanoparticles prevents the agglomeration, dissolution and shedding of the nanoparticles of the Pt alloy nanoparticles during the long-term operation of the fuel cell at low potential, significantly improving the durability of the Pt alloy nanomaterial. Finally, the rare earth oxide has good corrosion resistance under both acidic and alkaline conditions, and the rare earth oxide protective layer formed by deposition on the surface of the carbon carrier can effectively slow down the electrical corrosion of the carbon carrier at high potential, prevent the structural collapse of the carbon material, and significantly improve the structural stability of the Pt alloy nanomaterial.
[0143] Finally, it should be noted that the above preferred embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail through the above preferred embodiments, those skilled in the art should understand that various changes can be made in form and details without departing from the scope defined by the claims of the present invention.
Claims
1. A method for preparing a high compressive strain platinum alloy nanomaterial, characterized in that: The preparation method comprises the following steps: (1) adding a conductive carbon carrier, a morphology control agent, and a surfactant to a mixed liquid of ethanol and ultrapure water, and performing ultrasonic treatment to obtain a carbon carrier suspension; (2) adding the rare earth metal precursor solution to the carbon support suspension obtained in step (1) under stirring conditions, then performing ultrasonic mixing, and then adding an alkaline solution to obtain a mixed solution; (3) subjecting the mixed solution to ultrasonic and stirring treatments in sequence, and then subjecting the mixed solution to a hydrothermal reaction, so that the rare earth oxide nanoparticles are deposited on the surface of the conductive carbon support to form a rare earth oxide layer, and after the reaction, a carbon support / rare earth oxide nanoparticle composite is obtained; (4) adding the carbon support / rare earth oxide nanoparticle composite to a mixed solution of a platinum precursor and a transition metal precursor, and sequentially performing ultrasonic treatment and stirring to obtain a mixture slurry; (5) The mixture slurry is subjected to a hydrothermal reaction treatment or a hydrogen reduction heat treatment to alloy the platinum with the transition metal and deposit the platinum with the transition metal on the surface of the rare earth oxide layer to obtain a high compressive strain platinum alloy nanomaterial.
2. The method for preparing a high compressive strain platinum alloy nanomaterial according to claim 1, characterized in that: When the rare earth metal element in the rare earth metal precursor exchanges electrons with the non-metal element to form a compound, a metal valence change occurs.
3. The method for preparing a high compressive strain platinum alloy nanomaterial according to claim 1, characterized in that: The conductive carbon carrier includes a solid carbon carrier and / or a porous carbon carrier, wherein the solid carbon carrier is one of Cabot XC-72 and conductive carbon black; and the porous carbon carrier is one of Ketjen Black EC-300J, Ketjen Black EC-600JD, acetylene black and Cabot BP2000.
4. The method for preparing a high compressive strain platinum alloy nanomaterial according to any one of claims 1, 2 and 3, characterized in that: The morphology control agent is one of anhydrous citric acid, sodium citrate, potassium citrate, calcium citrate, ammonium citrate, diammonium hydrogen citrate, stearic acid, sodium dodecylbenzene sulfonate, quaternary ammonium compound, lecithin, amino acid type, betaine type, alkyl glucoside, fatty acid glyceride, fatty acid sorbitan and polysorbate, and the mass ratio of the morphology control agent to the conductive carbon carrier is 1 to 10:
1.
5. The method for preparing a high compressive strain platinum alloy nanomaterial according to any one of claims 1, 2 and 3, characterized in that: The surfactant is one of hexadecyltrimethylammonium bromide, hexadecyltrimethylammonium chloride, hexadecyl sodium sulfate, dihexadecyltrimethylammonium bromide, octadecyltrimethylammonium bromide, sodium octadecyl sulfate, heptadecyltrimethylammonium bromide, tetradecyltrimethylammonium bromide, dodecyltrimethylammonium bromide, sodium dodecyl sulfate, sodium dodecyl sulfonate, and dodecyltrimethylammonium bromide; and the mass ratio of the surfactant to the conductive carbon carrier is 1 to 10:
1.
6. The method for preparing a high compressive strain platinum alloy nanomaterial according to claim 1, characterized in that: In the step (1), the volume ratio of ethanol to ultrapure water is 1:9, and the concentration of the carbon carrier suspension is 1-10 mg / mL.
7. The method for preparing a high compressive strain platinum alloy nanomaterial according to claim 1, characterized in that: In the step (2), the alkaline solution is one of sodium hydroxide solution, potassium hydroxide solution, calcium hydroxide solution, and ammonia water, the mass ratio of alkali to conductive carbon carrier in the alkaline solution is 1 to 20:1, and the amount of rare earth metal precursor solution added is calculated based on the mass ratio of rare earth oxide to conductive carbon carrier satisfying 3:7; in the step (4), the molar concentration ratio of platinum precursor solution to transition metal precursor solution is 0.5 to 10:1, and the platinum concentration in the mixture slurry is 0.5 to 10 mg / mL.
8. The method for preparing a high compressive strain platinum alloy nanomaterial according to claim 1, characterized in that: In the step (3), the hydrothermal reaction temperature is 160°C, the hydrothermal reaction time is 2 hours, and after the hydrothermal reaction, the reaction product is filtered, washed, and vacuum dried in sequence; in the step (5), the hydrothermal reaction temperature is 100-200°C, the hydrothermal reaction time is 1-30 hours, and after the hydrothermal reaction, the reaction product is filtered, washed, vacuum dried, and acid washed in sequence. After the acid washing is completed, the reaction product is filtered, washed, and vacuum dried again. The hydrogen reduction heat treatment temperature is 250-900°C, the heat treatment time is 0.5-6 hours, and after the heat treatment is completed, the heat treatment product is acid washed, filtered, washed, and vacuum dried in sequence.
9. A high compressive strain platinum alloy nanomaterial, characterized in that: Prepared according to the preparation method according to any one of claims 1, 2, 3, 6, 7 and 8.
10. Use of the high compressive strain platinum alloy nanomaterial according to claim 9 in hydrogen-oxygen fuel cells and methanol fuel cells.